Applying tennis match statistics to increase serving performance during a match in progress - Pollard, G.; Pollard, G.; Barnett, T.; Zeleznikow, J. (Medicine and Science in Tennis, 2009)
In this article, we analyse the situation where a player takes a high level of risk on the first serve, and either a high or a low level of risk on the second serve. Similar analyses could be carried out for when a player takes a medium or low level of risk on either serve (although the risk on the second serve should always be no greater than that taken on the first serve). A player may deviate from the strategy of taking a high level of risk on the first serve as a surprise strategy, but this problem is not considered in this paper. The model considered here allows serving strategies that are dependent on the type of court surface and the serving and receiving capabilities of any two top players. The model is extended to allow for the possibility of players changing serving strategies throughout the match in progress. Practical suggestions are given for the use of these methods by elite players in order to increase their performance. In particular, match statistics are displayed on the scoreboard for the players to view, and these statistics can assist the players as to whether to use two high risk serves or a typical high risk first serve and low risk second serve. Given that coaching intervention is allowed in team competition, this creates even more opportunities for the use of technology to assist players in determining serving strategies.